Mortality and major disease risk among migrants of the 1991-2001 Balkan wars to Sweden: A register-based cohort study. - Edda Bjork Thordardottir; Li Yin; Arna Hauksdottir; Ellenor Mittendorfer-Rutz; Anna-Clara Hollander; Christina M Hultman; Paul Lichtenstein; Weimin Ye; Filip K Arnberg; Fang Fang; Emily A Holmes; Unnur Anna Valdimarsdottir (PLoS Medicine)
Background In recent decades, millions of refugees and migrants have fled wars and sought asylum in Europe. The aim of this study was to quantify the risk of mortality and major diseases among migrants during the 1991-2001 Balkan wars to Sweden in comparison to other European migrants to Sweden during the same period. Methods and findings We conducted a register-based cohort study of 104,770 migrants to Sweden from the former Yugoslavia during the Balkan wars and 147,430 migrants to Sweden from 24 other European countries during the same period (1991-2001). Inpatient and specialized outpatient diagnoses of cardiovascular disease (CVD), cancer, and psychiatric disorders were obtained from the Swedish National Patient Register and the Swedish Cancer Register, and mortality data from the Swedish Cause of Death Register. Adjusting for individual-level data on sociodemographic characteristics and emigration country smoking prevalence, we used Cox regressions to contrast risks of health outcomes for migrants of the Balkan wars and other European migrants. During an average of 12.26 years of follow-up, being a migrant of the Balkan wars was associated with an elevated risk of being diagnosed with CVD (HR 1.39, 95% CI 1.34-1.43, p < 0.001) and dying from CVD (HR 1.45, 95% CI 1.29-1.62, p < 0.001), as well as being diagnosed with cancer (HR 1.16, 95% CI 1.08-1.24, p < 0.001) and dying from cancer (HR 1.27, 95% CI 1.15-1.41, p < 0.001), compared to other European migrants. Being a migrant of the Balkan wars was also associated with a greater overall risk of being diagnosed with a psychiatric disorder (HR 1.19, 95% CI 1.14-1.23, p < 0.001), particularly post-traumatic stress disorder (HR 9.33, 95% CI 7.96-10.94, p < 0.001), while being associated with a reduced risk of suicide (HR 0.68, 95% CI 0.48-0.96, p = 0.030) and suicide attempt (HR 0.57, 95% CI 0.51-0.65, p < 0.001). Later time period of migration and not having any first-degree relatives in Sweden at the time of immigration were associated with greater increases in risk of CVD and psychiatric disorders. Limitations of the study included lack of individual-level information on health status and behaviors of migrants at the time of immigration. Conclusions Our findings indicate that migrants of the Balkan wars faced considerably elevated risks of major diseases and mortality in their first decade in Sweden compared to other European migrants. War migrants without family members in Sweden or with more recent immigration may be particularly vulnerable to adverse health outcomes. Results underscore that persons displaced by war are a vulnerable group in need of long-term health surveillance for psychiatric disorders and somatic disease.